An Assessment of the Vocabulary Knowledge of Students in the Final Year of Secondary Education. Is Their Vocabulary Extensive Enough? - Olmos, Carmen (International Journal of English Studies, 2009)
Several research studies have proven a direct relationship between the amount of words known by a foreign language student and his/her language proficiency. Therefore, knowing the amount of words that our students are acquainted with would help teachers to predict their general ability in the foreign language. The aim of this study is to determine the vocabulary size of a group final year students in a High School in Murcia. The instrument used to measure students’ vocabulary size was Nation’s Vocabulary Levels Test. This test has been validated on successive occasions. A total number of 49 students sat the exam in the case of the first test containing the 1000 and 2000 levels; and 38 sat the second test. The results obtained were poorer than expected.